Tubular linear switched reluctance actuator: Design and characterization - Md Ghazaly, Mariam; Yeo, Chin Kiat; Chong, Shin Horng; Hasim, Norhaslinda; Abdullah, Zulkeflee; Nordin, Nurdiana (Penerbit UTM Press, 2022)
Linear electromagnetic actuator is receiving significant attention due to recent advances in power electronics and modern control methods. This research proposes a three-phase tubular linear switched reluctance actuator (LSRA) for application in the semiconductor fabrication industry. The tubular LSRA has a robust construction, low manufacturing and maintenance cost, good fault tolerance capability, and high reliability in a harsh environment, making it an attractive alternative to a permanent magnet linear actuator. However, the tubular LSRA has a long mover, which increases the possibility of the mover deforming during fabrication. So, a new mover design is proposed to overcome the problem. The proposed mover design allows the traveling distance of the actuator to be modified by adding or removing the rings without changing the shaft. The tubular LSRA prototype is fabricated according to the optimized design. To drive the tubular LSRA, a appropriate switching algorithm method are used to provide the correct switching signal. This method is straightforward, while no extensive knowledge of power electronic converter is required. The developed tubular LSRA can generate a maximum static force of 0.65 N. Through the open-loop reciprocating motion, the dynamic responses of the tubular LSRA can achieve a maximum velocity of 210 mm/s and maximum acceleration of 8m/s2, which are in the performance range for precision mechanism.